2012
DOI: 10.1371/journal.pcbi.1002379
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cortisol Dynamics in the Neuro-endocrine Axis Distinguishes Normal, Depression, and Post-traumatic Stress Disorder (PTSD) in Humans

Abstract: Cortisol, secreted in the adrenal cortex in response to stress, is an informative biomarker that distinguishes anxiety disorders such as major depression and post-traumatic stress disorder (PTSD) from normal subjects. Yehuda et al. proposed a hypothesis that, in humans, the hypersensitive hypothalamus-pituitary-adrenal (HPA) axis is responsible for the occurrence of differing levels of cortisol in anxiety disorders. Specifically, PTSD subjects have lower cortisol levels during the late subjective night in comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
140
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(145 citation statements)
references
References 57 publications
1
140
0
4
Order By: Relevance
“…Borrowing from the field of systems engineering, robustness theory describes how architectural features of a system (in this case, negative cortisol feedback loops, adrenal/non-adrenal interactions, and 11␤-HSD and other enzymatic interactions) give rise to system functioning. Dynamic systems modeling has been used successfully within the context of HPA function (Aschbacher et al, 2012;Sriram et al, 2012;Vinther et al, 2011), as well as in predicting metabolic health (Aschbacher et al, 2014). This approach to modeling HPA activity in obesity may be more appropriate and is a promising avenue for future research.…”
Section: Resultsmentioning
confidence: 99%
“…Borrowing from the field of systems engineering, robustness theory describes how architectural features of a system (in this case, negative cortisol feedback loops, adrenal/non-adrenal interactions, and 11␤-HSD and other enzymatic interactions) give rise to system functioning. Dynamic systems modeling has been used successfully within the context of HPA function (Aschbacher et al, 2012;Sriram et al, 2012;Vinther et al, 2011), as well as in predicting metabolic health (Aschbacher et al, 2014). This approach to modeling HPA activity in obesity may be more appropriate and is a promising avenue for future research.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, investigations will more likely identify or model dynamics of different biomarkers or biosignatures that indicate the presence of clinically significant PTSD symptoms, associate with risk for PTSD after trauma exposure, and predict or identify recovery. 97 Protein, metabolic, as well as genetic and genomic candidate biomarkers are being sought, but none so far has been discovered that shows sufficient sensitivity for PTSD diagnosis as well as specificity (ie, little overlap with other psychiatric diagnoses). 40,98 The most replicated biomarker so far is a hypothalamic-pituitary-adrenal axis finding of low plasma cortisol (especially at the nadir), and increased glucocorticoid receptor sensitivity, a finding opposite that of MDD, despite commonalities that include central nervous system hyperarousal, increased amygdalar reactivity, and diminished parasympathetic outflow.…”
Section: The Use Of Biomarkers In the Diagnosis Of Ptsdmentioning
confidence: 99%
“…Authors Recommendations: The validity of this model can be more clearly demonstrated by comparing the model solution with the previously published data of cortisol dynamics in normal and post-traumatic stress disorder (PTSD) in references ( [53] and [16]). …”
Section: Reviewers' Commentsmentioning
confidence: 99%
“…These models [13,14,16] incorporate positive self-regulation of glucocorticoid receptor expression in the pituitary, which may generate bistability in the dynamical structure of the model [17]. Of the two stable equilibrium states, one is characterized by higher levels of cortisol and is identified as the "normal" state.…”
Section: Introductionmentioning
confidence: 99%